Design, synthesis and biological evaluation of functionalized phthalimides: A new class of antimalarials and inhibitors of falcipain-2, a major hemoglobinase of malaria parasite. Issue 8 (15th April 2015) - Singh, Anil K.; Rajendran, Vinoth; Pant, Akansha; Ghosh, Prahlad C.; Singh, Neelu; Latha, N.; Garg, Sandeep; Pandey, Kailash C.; Singh, Brajendra K.; Rathi, Brijesh
Graphical abstract: Abstract: Phthalimides functionalized with cyclic amines were synthesized, characterized and screened for their in vitro antimalarial efficacy against Plasmodium falciparum ( Pf 3D7). Of all the listed phthalimides evaluated, 14 and24 were identified as potent antimalarial agents as advocated by assessment of their ability to inhibit [ 3 H] hypoxanthine incorporation in the nucleic acid of parasites. In addition, phthalimides14 and24 were incubated for 60 and 90 h and an enhanced antimalarial effect was noticed with increase in time to great extent. A reduction in IC50 values was observed with increase in exposure time of the parasite to the compounds. A symmetric phthalimide, 24 possessing piperazine as linker unit was identified as the most potent antimalarial agent with IC50 values of 5.97 ± 0.78, 2.0 ± 1.09 and 1.1 ± 0.75 μM on incubation period of 42, 60 and 90 h, respectively. The abnormal morphologies such as delay in developmental stages, growth arrest and condensed nuclei of parasite were observed with the aid of microscopic studies upon exposure with14 and24 . The evaluation of14 and24 against chloroquine resistant strain, ( Pf 7GB) of P. falciparum afforded IC50 values, 13.29 ± 1.20 and 7.21 ± 0.98 μM, respectively. The combination of24 with artemisinin (ART) showed enhanced killing of parasite against Pf 3D7. Further, all phthalimides were evaluated for their activity against falcipain-2 (FP2), a major hemoglobinase of malarial parasite. The enzymatic assay afforded6 as most active member against FP2. To the best of our knowledge this is the initial study represents phthalimide protected amino acids functionalized with cyclic amines as potent antimalarial agents.